GANGGUAN MUSKULOSKELETAL BAGI PETANI DI KABUPATEN JEMBER - Luh Titi Handayani (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: Farmers' activities while working in the fields are related to positions that tend to be static for a long time and continuously. This condition can cause injury to the musculoskeletal system (musculoskeletal disorder). The purpose of this study is to identify forms of musculoskeletal disorders which are included in occupational diseases.Methods: The research method is descriptive with population and samples. The research was conducted on 110 farmers in the working area of the Jember RegencyResults: The results showed that 67.6% had less than optimal work quality, the incidence of musculoskeletal disorders found that 57% had high complaints and 10% had very high complaints and complaints. The largest is at the waist by 39%.Conclusion: The study concluded that a static position for a long time can cause disorders of the musculoskeletal system. Recommendations in this study are expected to regulate work position as a factor that must be considered in research related to musculoskeletal disorders.